Association on DISC1 SNPs with schizophrenia risk: A meta-analysis. (December 2018) - Ma, Jia-Hui; Sun, Xiao-Yu; Guo, Tong-Jun; Barot, Emily; Wang, Dong-Fang; Yan, Lai-Lai; Ni, Da-Wei; Huang, Ning-Hua; Xie, Qing; Zeng, Jing; Ou-Yang, Li; Liu, Ya-Qiong; et al.
Highlights: The meta-analysis aimed to assess the associations between DISC1 SNPs and schizophrenia based on 5 candidate SNPs. SNP rs821597 is associated with schizophrenia risk in terms of both allelic and genotypic distribution. SNP rs821616 is associated with schizophrenia risk in terms of genotypic distribution, especially in cases above 40 years old. Abstract: Schizophrenia is a major psychiatric disorder with complex genetic, environmental, and psychological etiologies. Although DISC1 gene has been shown as a risk factor for schizophrenia in some reports, there is a lack of a consensus. We therefore performed separate meta-analyses aiming to assess the associations between DISC1 SNPs and schizophrenia risk. We found that SNP rs821597 is significantly associated with schizophrenia risk in terms of both allelic and genotypic distribution, while SNP rs821616 is associated with schizophrenia in terms of genotypic distribution, especially in cases above 40 years old.